How to choose the right person for the right job every time - Davila, Lori; Kursmark, Louise (2004)
Contiene: Your hiring decisions will either make or break your company. Take the guesswork out of hiring with bahavior-based interviewing. The bahavior-based interview in five easy steps. Interview questions. Six companies that successfully use behavior-basd interviewing. A review of legal guidelines for interviewing candidates.
Keywords: Recursos Humanos